Analisis Perubahan Kurikulum IPA SD dari Tahun 1990-2025 : A Systematic Literature Riview - Sudarto, Sudarto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is a qualitative study employing the Systematic Literature Review (SLR) method, analyzing 20 SINTA 1-6 journal articles on changes in the Natural Science curriculum for Elementary Schools in Indonesia from 1990-2025. The study aims to identify transformation patterns in the Natural Science Elementary curriculum from KBK 1994 to Kurikulum Merdeka 2025, classify the dominant learning models, analyze supporting-inhibiting implementation factors, and construct trends in educational paradigm shifts for IPA instruction. Data analysis techniques utilized qualitative content analysis combined with quantitative meta-synthesis through four PRISMA stages (searching 1,247 articles to screening 156 to full-text selection of 20 articles). Analysis employed descriptive-thematic approaches with classification matrices (curriculum periods, learning models, factors, trends), flexibility-effectiveness correlation, and triangulation of policy documents such as Permendikdasmen No.12/2025. Results: Dominance of Kurikulum Merdeka (55%) addresses weaknesses of KBK-KTSP (20%: content overload) and K13 (25%: teacher-centered). Project-based/IPAS excels (40%) improving learning outcomes, student participation, and creativity. Supporting factors include school autonomy, 3-component RPP, digitalization; inhibiting factors: 3T infrastructure, teacher readiness. Trend 2020-2025: teacher-centered to scientific to student-centered/IPAS. Conclusion: Kurikulum Merdeka optimizes historical transformation of IPA SD from fragmented memorization to holistic IPAS exploration, proven effective and strongly correlated or aligned with Vygotsky-Dewey constructivism. Practical implications provide SD teachers with IPAS-project character blueprint priorities, school principals leverage local autonomy, and policymakers focus on 3T digital training. This research serves as a compass for Kurikulum Merdeka toward quality SD science literacy, preparing critical generations for SDGs 4.7 and Indonesia Golden 2045.